2014
DOI: 10.1155/2014/437867
|View full text |Cite
|
Sign up to set email alerts
|

Distensibility and Strength of the Pelvic Floor Muscles of Women in the Third Trimester of Pregnancy

Abstract: Objective. The objective of this study was to compare the role of the pelvic floor muscles between nulliparous and multiparous women in the third trimester of pregnancy, by analyzing the relationship between electrical activity (surface electromyography—EMG), vaginal palpation (modified Oxford scale), and perineal distensibility (Epi-no). Methods. This was an observational cross-sectional study on a sample of 60 healthy pregnant women with no cervical dilation, single fetus, gestational age between 35 and 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
1
15
0
15
Order By: Relevance
“…Zanetti, et al 23 found greater distensibility in the multiparous than in the nulliparous women (20.07 (SD 0.46) cm vs 19.3 (SD 2.8) cm; p<0.001) during delivery. In addition, previous study conducted by Petricelli, et al 24 suggested that nulliparous women had higher electrical activity compared to multiparous women. The mechanical and hormonal effects of pregnancy may induce biomechanical, neurological or neuromuscular changes to the pelvic floor and pelvic organ supports 25,26 and they may contribute to pelvic floor dysfunction, independently of delivery mode.…”
Section: Discussionmentioning
confidence: 85%
“…Zanetti, et al 23 found greater distensibility in the multiparous than in the nulliparous women (20.07 (SD 0.46) cm vs 19.3 (SD 2.8) cm; p<0.001) during delivery. In addition, previous study conducted by Petricelli, et al 24 suggested that nulliparous women had higher electrical activity compared to multiparous women. The mechanical and hormonal effects of pregnancy may induce biomechanical, neurological or neuromuscular changes to the pelvic floor and pelvic organ supports 25,26 and they may contribute to pelvic floor dysfunction, independently of delivery mode.…”
Section: Discussionmentioning
confidence: 85%
“…Quando o objetivo é o alongamento da musculatura do assoalho pélvico e preparação para o parto (classificado como treinamento) os estudos investigaram a relação entre a utilização do dispositivo e diminuição das taxas de episiotomia e lacerações perineais de acordo com Kovacs et al 14 , Kok et al 15 , Ruckhäberle et al 16 , Shek et al 17 , Kamisan et al 8 . Já a avaliação da distensibilidade da musculatura do assoalho pélvico (classificada como avaliação) em gestantes e parturientes está relacionada com a justificativa ou não a necessidade de episiotomia segundo Petricelli et al 18 , Kubotani et al 19 , Nakamura et al 20 e Zanetti et al 2 .…”
Section: Resultsunclassified
“…A idade gestacional de início da utilização do dispositivo Epi-No para treinamento foi de 37 semanas, com período de aplicação variando entre uma vez ao dia durante quatorze dias, por quinze minutos [14][15][16] ; duas sessões de vinte minutos por dia até o parto 17 ; e duas vezes ao dia durante vinte minutos totalizando a média de utilização de quatorze dias 8 . Quando utilizado como método de avaliação o teste foi realizado uma única vez e a partir de 20 semanas de gestação a até o período de dilatação (trabalho de parto) 2,[18][19][20] .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Table 1 summarizes the results of the methodological quality assessment. Luginbuehl et al 20 Pereira et al 21 Petricelli et al 22 -Resende et al 23 Resende et al 24 -Sapsford, Richardson, Maher and Hodges 25 Smith, Coppieters and Hodges 26 Smith, Coppieters and Hodges 27 Soljanik et al 28…”
Section: Study Selectionmentioning
confidence: 99%